Nationalism in Tasawuf Communities: The Meaning Of Nation's Monuments As The National Agreement In Tarekat Shiddiqiyyah - Budi, Setiawan; Warsono, Warsono; Purnomo, Nugroho Hari (International Journal for Educational and Vocational Studies, 2020)
In the modern era one of the big problems faced by the Indonesian nation and state is the fading of nationalism and Pancasila values. Actualization of Pancasila and nationalism values of the Indonesian people continues to be encouraged with the aim of preserving and passing on to the nation's next generation. One example is done by the Shiddiqiyyah Order in Ploso District, Jombang Regency. The Shiddiqiyyah Tarekat, led by Kyai Muchtar Mu'thi, has actualized the values of Pancasila and nationalism with various forms. One form of actualization is in the form of national monument buildings. The problems discussed in this research are How can the meaning of the nation monument as a form of nationalism in Shiddiqiyyah Tarekat? This study uses a qualitative method based on the philosophy of phenomenology about the meaning of Alfred Schutz . The spatial limitation of this research is the Shiddiqiyyah Tarekat Center located in Losari Village, Ploso District, Jombang Regency. While the benefits of this research are to increase the repertoire of research on phenomena in Sufism and as a reference material for nationalism education in Indonesia in the modern era. The results of the study are the Shiddiqiyyah teaches the value of nationality, nationalism and Pancasila because it is a manifestation of the practice of "Hubbul Wathon Minal Faith". Based on these traditions, Shiddiqiyyah teaches the value of Pancasila and Nationalism to its membersWhile the meaning of these monuments is a manifestation of the spirit of nationalism and the love of Pancasila from members of the Shiddiqiyyah Tarekat to unite faith and humanity.